2022
DOI: 10.3390/ani12223147
|View full text |Cite
|
Sign up to set email alerts
|

Gene and Protein Accumulation Changes Evoked in Porcine Aorta in Response to Feeding with Two Various Fructan Sources

Abstract: In this study, two different ITFs sources were incorporated into a cereal-based diet to evaluate possible aortic protein and gene changes in nursery pigs. The animals were fed two different experimental diets from the 10th day of life, supplemented with either 4% of dried chicory root (CR) or with 2% of native inulin (IN). After a 40-day dietary intervention trial, pigs were sacrificed at day 50 and the aortas were harvested. Our data indicate that dietary ITFs have the potential to influence several structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Various studies have shown that both DF and hyperlipidemia have a significant impact on the endothelial expression of TXNDC5, and also TXNDC5 mediates TNF-α-induced NOX activation in ECs [43,182,184]. However, the TXNDC5 protein level, when exposed to aeroplysinin-1 as a modulator of the redox balance in ECs, is downregulated [185], and a chicory root diet increased it in porcine aorta [186]. TXNDC5 promotes endothelial activation and atherogenesis induced by DF.…”
Section: Txndc5 and Heart Diseasesmentioning
confidence: 99%
“…Various studies have shown that both DF and hyperlipidemia have a significant impact on the endothelial expression of TXNDC5, and also TXNDC5 mediates TNF-α-induced NOX activation in ECs [43,182,184]. However, the TXNDC5 protein level, when exposed to aeroplysinin-1 as a modulator of the redox balance in ECs, is downregulated [185], and a chicory root diet increased it in porcine aorta [186]. TXNDC5 promotes endothelial activation and atherogenesis induced by DF.…”
Section: Txndc5 and Heart Diseasesmentioning
confidence: 99%